Analisis Pengaruh Budaya Organisasi dan Kompetensi Pegawai Terhadap Kinerja: Implikasi terhadap Komitmen Organisasi (Studi Kasus pada Rumah Sakit Umum di DKI Jakarta) - Hanafi, Imam; Padang, Nely Salu; Soesanto, Dasa Rahardjo; Qadafi, Muamar (Jurnal EMT KITA, 2023)
This study aims to analyze the impact of organizational culture and employee skills on performance, as well as the implications for organizational commitment in general hospitals (RSUs) in the DKI Jakarta region. This study took medical and paramedical staff as a sample, used a questionnaire as a research tool, and applied census techniques by taking the entire population as a sample. The analysis method used is hierarchical linear modeling (HLM) to evaluate the influence of related variables. Research results show that organizational culture and employee skills have a significant impact on performance and have a positive impact on organizational commitment. In addition, organizational commitment also partly mediates the effects of organizational culture and employee skills on performance. These results provide important information for developing hospital management policies aimed at improving organizational performance and commitment.